/ = pe
• =ori
1/2 • [1/2 •(1/2x -1) -1] +1 = 5/4
Răspunsuri la întrebare
Răspuns de
2
1/2 × [1/2 × (x/2 - 1) - 1] + 1 = 5/4
1/2 × [1/2 × (x-2)/2 - 1] + 1 = 5/4
1/2 × [(x-2)/4 - 1] + 1 = 5/4
1/2 × (x-2-4)/4 + 1 = 5/4
1/2 × (x-6)/4 + 1 = 5/4
(x-6)/8 + 1 = 5/4 |×8
x - 6 + 8 = 10
x = 10 + 6 - 8
x = 8
1/2 × [1/2 × (x-2)/2 - 1] + 1 = 5/4
1/2 × [(x-2)/4 - 1] + 1 = 5/4
1/2 × (x-2-4)/4 + 1 = 5/4
1/2 × (x-6)/4 + 1 = 5/4
(x-6)/8 + 1 = 5/4 |×8
x - 6 + 8 = 10
x = 10 + 6 - 8
x = 8
Alte întrebări interesante
Engleza,
8 ani în urmă
Fizică,
8 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Engleza,
9 ani în urmă